Enhancing Hand Cleaning During Dental Visit Through Nudging - Malik, Normaliza Ab; Abdul Kadir, Nor Bayah (International Journal of Human and Health Sciences (IJHHS), 2023)
Background: Hand washing or hand-cleaning is a behaviour that has not been performed routinely as a habit for everyone, but its importance has been greatly emphasised during the COVID-19 outbreak. Nudges in the form of prompts, cues and reminders have been used to encourage hand cleaning. Objective: To improve hand-cleaning to prevent transmission of the disease during dental visits through nudge. Methods: This experimental, observational pilot study was conducted at private dental practices. Hand sanitisers were placed at a few places in the clinic to encourage hand cleaning. Hand sanitiser was not placed outside the treatment room during the baseline data collection. The patients’ behaviour in using the hand sanitisers was observed and analysed. Results: A total of 130 participants were involved in the study, with more than half being female (59.2%) and above 35 years old (60.8%). More than half of the participants performed hand cleaning behaviour immediately after treatment (68.2%). However, there was no significant difference between those who performed the hand cleaning when the hand sanitiser was placed in the waiting room and front of the treatment room (P>0.05). Placing the hand sanitiser in front of the dental treatment room increased the likelihood of hand cleaning. However, there was no significant difference (OR: 3.4, 95%CI: 1.09-10.7, p<0.05). Conclusion: This study has shown the potential effect of using a nudge to encourage hand cleaning after dental treatment by placing an additional hand sanitiser in front of the dental treatment room. Despite the increase in the number of people using the hand sanitiser immediately after treatment, there is limited evidence on the long-term effect of this measure, and therefore, long-term research is warranted. International Journal of Human and Health Sciences Vol. 07 No. 03 Jul’23 Page: 239-243